Restricted substances for textiles. Issue 1 (29th August 2022) - Patra, Arun Kumar; Pariti, Siva Rama Kumar
Abstract: Awareness of the harmful effects of chemical substances is gradually increasing and scientific investigations have time and again revealed the negative influences of the chemicals conventionally used. This has led to restricting the use of certain chemicals and dyes in textile wet treatments. Globally there has been an acceptance of this by branding agencies and retailers. Government organisations have also supported these restrictions, and curtailment in such chemical usage has now become the norm throughout the textile supply chain. This issue of Textile Progress reviews the chronological evolution of the restrictions leading to the concepts of RSL (Restricted Substances List) and MRSL (Manufacturing Restricted Substances List) now widely followed. The listing of harmful chemicals under Substances of Very High Concern (SVHC) is also discussed. The major chemicals or groups of chemicals facing restriction are dealt with in detail, covering their usage, hazards, sources, chemistry and possible substitutes (if any). Examples such as the alkyl phenols and alkyl phenol ethoxylates used for decades as detergents and wetting agents in preparatory processes, dyeing and printing were found to be potential hormone disruptors and very toxic to aquatic life, and substitutes have been put in place. Substances such as azo-amines, chlorophenols, formaldehyde, brominated flame retardants, heavy metals and fluorochemicals also have their share of adverse effects on human health and environment and need to be avoided. Studies have shown the presence of phthalates in routinely-used chemicals which can be traced back to the manufacturing process itself and other hazardous chemicals such as bisphenols, chloroparaffins, polycyclic aromatic hydrocarbons, quinoline, VOCs (Volatile Organic Compounds), biocides and UV absorbers have also figured in discussions. Comprehensive testing for the presence of the various restricted substances is essential but anomalies can arise.